Examining Resilience-Focused Interventions for Rural Populations Experiencing Chronic Stress: A Mixed Methods Systematic Review Protocol - Cameranesi, Margherita; Adisaputri, Gianisa; Jefferies, Philip; Ungar, Michael (European Journal of Applied Sciences, 2023)
This article describes the protocol of a mixed methods systematic review of resilience-focused interventions for children, youth, and adults exposed to chronic stress in rural contexts that was prospectively registered with PROSPERO (reference number CRD42021292413). The review will be performed using a convergent segregated mixed methods approach within which an intervention review and a qualitative evidence synthesis will be combined, and a results-based convergent synthesis design will be used to synthesize the data extracted from all included studies. The mixed methods systematic review will conform to the guidelines outlined by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 statement, which were used to guide the development of this review protocol and reporting of the review findings. Additionally, the Johanne Briggs Institute methodological guidelines for conducting mixed methods reviews using a segregated approach will be implemented throughout the review process. The review will contribute to a better understanding of the available resilience-focused interventions for children, youth, and adults who experience chronic stress in rural contexts by investigating what interventions work for which populations (i.e., children, youth, or adults) in what circumstances (i.e., in the context of exposure to different chronic stressors).